The significance of study of sports media discourse in higher educational institutions (Eurasian Journal of Philology Science and Education, 2023)
This article is devoted to the importance of studying such a rather broad concept as sports discourse. Today, sport is one of those spheres of society, acquaintance with which is carried out mainly through the media space. Sports activities are developing daily, and the media sphere is developing along with it. Sports events play an important role in the development of the culture of the country and people, and sport may beconsidered as a factor in communication between cultures. The purpose of this article is to determine the frequency of the use of sports discourse by students in higher educational institution in the academic sphere and in everyday life. A significant role in the implementation of the use of sports discourse is played by communication, in particular speech. The objects of the research are sports discourse and sports media discourse. In this research there was done comparative analysis of the results of the questionnaire, where statistics were shown on the use of sports discourse at the university level. The results of the study can be used in the  development of contextual understanding of sports blogs, sports news channels and the speech of sports event commentators in a foreign language. In addition, the results of the article can be used to compile teaching aids and guidelines for the study of sports discourse.Key words: sports discourse, media discourse, intercultural communication, discourse analysis, sport speech.